Capacity Building Of Dalit Women In Lucknow District : A Case Study In BKT Block (International Journal of Scientific Research and Management (IJSRM), 2017)
Capacity building often refers to assistance that is provided to entities, usually societies in developing countries, which have a need to develop a certain skill or competence, or for general upgrading of performance ability of women. It involves activities which strengthens the abilities, skills and behavior of women and improve them so that they can meet its mission and goals in a sustainable way. It is a creation of an enabling environment with appropriate policy and legal framework, institutional development including community participation (especially women). It is a long term, continuous process of developing Skill and competence. Dalit women in India is heavily dependent on many different variables which enable them to function them independently to equip women to all attribute. This paper is a small exploratory design to analyze and interpret comparative study between Ambedkar and Non Ambedkar Gram of Lucknow District. The sample size will be 500 dalit women of which 250 are for non Ambedkar Gram. A selected of random basis. The analysis is done on the major factor and result supported the hypothesis which is discussed in the full length paper.